Identification and expression analysis of pineapple sugar transporters reveal their role in the development and environmental response - Fakher, Beenish; Jakada, Bello Hassan; Greaves, Joseph G.; Wang, Lulu; Niu, Xiaoping; Cheng, Yan; Zheng, Ping; Aslam, Mohammad; Qin, Yuan; Wang, Xiaomei (Frontiers in Plant Science, 2022)
In plants, sugars are required for several essential functions, including growth, storage, signaling, defense and reproduction. Sugar transporters carry out the controlled movement of sugars from source (leaves) to sink (fruits and root) tissues and determine the overall development of the plant. Various types of sugar transporter families have been described in plants, including sucrose transporters (SUC/SUT) and monosaccharide transporters (MST). However, a detailed inventory of pineapple sugar transporters remains unavailable. This study systematically identified and classified 45 MST and 4 SUC/SUT genes in the pineapple genome. We found that the expression patterns of sugar transporters genes have a spatiotemporal expression in reproductive and vegetative tissues indicating their pivotal role in reproductive growth and development. Besides, different families of sugar transporters have a diel expression pattern in photosynthetic and non-photosynthetic tissues displaying circadian rhythm associated participation of sugar transporters in the CAM pathway. Moreover, the deregulation of the crucial stress-related sugar transporters during cold stress might be contributing to cold tolerance in pineapple. The information provided here could be utilized to regulate the candidate genes to develop disease-free, cold-resistant, superior quality next-generation pineapple crop.